An Analysis of the Sector; Digital Interfaces and Techniques Used in the Design Offices. - Ardatürk, Ahmet Şadi (Electronic Turkish Studies, 2026)
Humans, who have developed the ability to exist in nature by compensating for their lack of innate abilities with their intellect, have been designing and producing since the dawn of time. Throughout history, many different techniques have been used to realize the potential of design, which is essentially a collection of organizations, and production, which enables this organization to exist in reality. In the field of design, technique can be defined, in its most basic sense, as any method used to make what exists in the mind visible. In other words, we can refer to the entirety of all instruments such as drawings, models, mockups, computeraided systems, etc., and the ways in which these instruments are used as techniques. The primary aim of this study is to explore and identify the techniques employed within the design process in the fields of industrial design and product design, to collect data on their application, to measure their efficiency, and, in this context, to establish a bridge between sectoral data and academic knowledge-particularly in relation to design education. At its core, the study seeks to generate insights that can guide academia through the systematic analysis of the collected data. Data were gathered from 83 firms actively producing for the domestic market in Türkiye, each employing industrial or product designers, regardless of their business volume, level of corporatization, or specific design sector. Additionally, 16 face-to-face interviews were conducted. While these in-depth interviews played a crucial role in uncovering the general processes and operational structures, further quantitative and qualitative data were obtained from the remaining firms through phone interviews and surveybased communication methods. The research data was divided into four main sections (drawing and mockups, 3D modeling, photorealistic image creation, graphic data processing, and presentation preparation) plus a supplementary section (artificial intelligence tools and design process collaboration). Furthermore, this research and study, including the entire process, content, interviews, methods, and conversion of data into findings, has been reviewed by the Istanbul Aydın University Social and Human Sciences Ethics Committee and received ethical approval at its meeting dated February 20, 2025, under number 2025/2. Meaningful data was converted into graphs showing percentages, multipliers, usage, frequency, and efficiency of numerical values. At this point, both the modes of use and the output characteristics of the AI tools were incorporated into the study as a techniccal component, since they were involved at multiple stages of the research process. As a result of the study, recommendations were made that are expected to contribute to academia and undergraduate education, along with quantitative and qualitative data on the techniques.